2012
DOI: 10.1148/radiol.12111494
|View full text |Cite
|
Sign up to set email alerts
|

Readout-segmented Echo-planar Imaging Improves the Diagnostic Performance of Diffusion-weighted MR Breast Examinations at 3.0 T

Abstract: DW imaging based on readout-segmented echo-planar imaging provided significantly higher image quality and lesion conspicuity than single-shot echo-planar imaging by reducing geometric distortions, image blurring, and artifact level with a clinical high-field-strength MR imager. Thereby, readout-segmented echo-planar imaging reached a higher diagnostic accuracy for the differentiation of benign and malignant breast lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
188
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 187 publications
(210 citation statements)
references
References 48 publications
18
188
4
Order By: Relevance
“…Ideally, ten or more b values are needed for better fitting performance. To further optimize diffusion-weighted imaging for BAT/BRITE characterization, faster and more robust DWI sequences, such as multi-shot EPI [40] and zoomed-DW EPI [41,42], may be needed to obtain multiple b value acquisitions to improve signal fitting accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, ten or more b values are needed for better fitting performance. To further optimize diffusion-weighted imaging for BAT/BRITE characterization, faster and more robust DWI sequences, such as multi-shot EPI [40] and zoomed-DW EPI [41,42], may be needed to obtain multiple b value acquisitions to improve signal fitting accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…MP 18 FDG PET-MRI datasets were assessed according to the following criteria. Both readers, in consensus, determined the probability of malignancy for MP 18 FDG PET-MRI data as previous studies have shown very good intra-and interobserver agreement by using the following evaluation of each imaging parameter (17,20). The readers were aware that the patients had a breast tumor, but they were provided with neither the previous mammographic and sonographic imaging data nor the histopathologic results.…”
Section: Discussionmentioning
confidence: 99%
“…DCE-MRI of the breast provides high-resolution anatomic information and enables the depiction of increased microvascular density and capillary leaks in malignant breast tumors as a marker of neoangiogenesis (29). DWI depicts cellular diffusivity, which is typically restricted in malignant tissue (7,20). 3D 1 H-MRSI detects elevated levels of the metabolite choline as a marker of an increased cell membrane turnover (6).…”
Section: Discussionmentioning
confidence: 99%
“…This method provides images with less artefacts and higher resolution for the evaluation of brain, brain stem and the breast [11][12][13]. However, to the best of our knowledge, its effectiveness in the evaluation of middle-ear cholesteatoma has not been established, yet.…”
Section: Introductionmentioning
confidence: 99%